Acetylated Dendrobium huoshanense polysaccharide: a novel inducer of apoptosis in colon cancer cells via Fas–FasL pathway activation and metabolic reprogramming - Yao, Liang; Gu, Chen; Ge, Ruipeng; Zhang, Xiaoqian; Meng, Xinqian; Wang, Lei; Peng, Daiyin; Li, Guozhuan (Frontiers in Oncology, 2025)
IntroductionNot all polysaccharides function as antitumor drugs, nor do they universally possess the same advantages regarding safety and biocompatibility. Those polysaccharides that are effective antitumor agents typically demonstrate superior safety profiles and biocompatibility compared to synthetic anticancer drugs, which can exhibit high toxicity and harmful side effects. Dendrobium huoshanense polysaccharide (DHP) has been recognized for its potential bioactive properties, particularly in anti-tumor treatment. This study investigates the effects of DHP on the proliferation and apoptosis of HCT116 colon cancer cells.MethodsDHP was extracted according to previously published experimental methods. The inhibitory effects of DHP were evaluated using IEC6, Caco-2, and HCT116 cell lines, with changes in cell morphology observed via transmission electron microscopy. After establishing the conditions for DHP administration, flow cytometry was employed to assess its effects on apoptosis, reactive oxygen species (ROS), and mitochondrial membrane potential of HCT116 cells. Additionally, immunoprecipitation, quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting, and biomarker detection were utilized to investigate the mechanisms underlying DHP’s inhibition of HCT116 cells and its impact on metabolic reprogramming.ResultsIn the present study, we observed that DHP treatment at 600 μg/ml for 24 h reduced HCT116 cell viability to 54.87%. In contrast, the inhibitory effect of DHP on the viability of IEC6 and Caco-2 cells was relatively mild. The specific mechanism involves DHP activating the mitochondrial apoptotic pathway leading to the downregulation of key metabolic intermediates and enzymes such as uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) and ST6Gal-I. By inhibiting ST6Gal-I activity, DHP activates the Fas/FasL signaling pathway. Additionally, DHP-induced ROS production effectively triggers apoptosis in HCT116 cells.ConclusionOur study demonstrates that DHP effectively inhibits the proliferation and induces apoptosis in HCT116 colon cancer cells through the activation of the Fas–FasL signaling pathway and metabolic reprogramming. The selective inhibitory effect of DHP on HCT116 cells, the activation of both death receptor and mitochondrial apoptotic pathways, and the modulation of metabolic reprogramming provide novel insights into the potential therapeutic strategies for colon cancer.